2000
DOI: 10.3354/dao039155
|View full text |Cite
|
Sign up to set email alerts
|

Reduced superoxide dismutase activity in Palaemonetes argentinus (Decapoda, Palemonidae) infected by Probopyrus ringueleti (Isopoda, Bopyridae)

Abstract: Cellular oxidative stress may promote damage or death in biological systems and may be caused by production of pro-oxidant molecules known as reactive oxygen species (ROS). , 1987), a gill chamber parasite known for its capacity to cause host metabolic changes, including changes in oxygen consumption rates. Infested and non-infested shrimp were collected in the Patos Lagoon estuary (southern Brasil), where the prevalence of the paraslte may be as high as 70%. No significant differences were observed for eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 12 publications
1
37
0
Order By: Relevance
“…On the other hand, carbohydrates appear to be of great importance, because the glycogen concentration was significantly higher (p < 0.05) in parasitized shrimp. Carbohydrate dependency in parasitized shrimp could be a reflex to the lower ability to oxidize lipids, especially considering that bopyrid isopods cause respiratory impairment to their hosts (Anderson 1975, Schuldt & Rodrigues-Capítulo 1987, Neves et al 2000.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, carbohydrates appear to be of great importance, because the glycogen concentration was significantly higher (p < 0.05) in parasitized shrimp. Carbohydrate dependency in parasitized shrimp could be a reflex to the lower ability to oxidize lipids, especially considering that bopyrid isopods cause respiratory impairment to their hosts (Anderson 1975, Schuldt & Rodrigues-Capítulo 1987, Neves et al 2000.…”
Section: Discussionmentioning
confidence: 99%
“…The authors attributed this response to the increased metabolic activity of infected fish. Shrimp Palaemonetes argentinus infected with the isopod Probopyrus ringueleti exhibited lower activity of the antioxidant enzyme superoxidase dismutase, which presumably lowers the capacity of the organism to deal with reactive oxygen species and thus to prevent cellular damage (Neves et al 2000). Other examples are reviewed in Sures (2004), who also recently reviewed the influence of parasites on biomarkers and discussed their possible impact on the physiological homeostasis of their hosts.…”
Section: Discussionmentioning
confidence: 99%
“…This was followed by a decrease of the antioxidant levels below control values at 48-72 h. This is similar to those studies related to oxidative stress such as pollution, bacterial infections, decrease of oxygen content in culture tanks, or the use of immunostimulants. Neves et al [42] reported a significant decrease in SOD activity when shrimp (Palaemonetes argentinus Nobili, 1901) was infected by Probopyrus ringueleti. Macmillan-Crow [43] suggested that inhibition of Mn-SOD activity by peroxynitrite could be related to numerous disease states.…”
Section: Generation Of Superoxide Anion and Sod Activitymentioning
confidence: 99%